2008
DOI: 10.1111/j.1601-0825.2007.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation in rat calvaria ceases within a limited period regardless of completion of defect repair

Abstract: A bone defect that is not repaired with bone completely is designated a non-union defect or a critical-size defect. The biological mechanism that regulates the process of bone repair of the critical-size defect remains unknown. The present study was designed to investigate bone repair in a critical-size defect compared with that in a smaller or non-critical-size defect. Our original standardized rat calvarial bone defect model was used for the experiment. The rate of bone formation was examined with X-ray morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
2
37
0
2
Order By: Relevance
“…Osteoblasts and osteocytes may cease degradation of ECM within a limited period, regardless of completion of the defect repair in the rat model, as we previously reported for production of ECM (Honma et al, 2008). Further investigation with this experimental model may help provide a greater understanding of the cellular and molecular events associated with the remodeling of the ECM during bone healing.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Osteoblasts and osteocytes may cease degradation of ECM within a limited period, regardless of completion of the defect repair in the rat model, as we previously reported for production of ECM (Honma et al, 2008). Further investigation with this experimental model may help provide a greater understanding of the cellular and molecular events associated with the remodeling of the ECM during bone healing.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous study using in situ hybridization demonstrated that osteoblasts and osteocytes no longer express bone matrix proteins in the repairing process of rat calvarial bone defects, and then bone healing ceases within a limited period, regardless of completion of the defect repair (Honma et al, 2008). However, how long osteoblasts and osteocytes keep producing bone matrix proteins, such as type I collagen and osteocalcin during the healing process, was not known.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations